Spatiotemporal effects of proximity to metro extension on housing price dynamics in Manhattan, New York City - ChengHe Guan; Mark Junjie Tan; Richard Peiser (Journal of Transport and Land Use)
Investment in public transportation such as a metro line extension is often capitalized partially into housing values due to the spatiotemporal effects. Using housing transaction data from 2014 to 2019, this paper studies the Second Avenue Subway or Q-line extension in New York’s City’s Manhattan borough. Multiple metro station catchment areas were investigated using spatial autocorrelation-corrected hedonic pricing models to capture the variation of housing price dynamics. The results indicate that properties in closer proximity to the Q-line extension received higher price discounts. The effect varied by occupancy type and building form: condominiums experienced the highest price discount, while walk-up and elevator co-ops experienced a price premium. After controlling for location variations, we observed price discounts on the westside and price premiums on the eastside of the Q-line. Residential properties within 150 m west to the Q-line extension received the highest price discount post operation, while on the eastside, properties in the same proximity received the highest price premium. The anticipation effect varies by distance to metro extension stations, both before and after the operation of metro line extension. We discuss the disruption of metro construction on the housing market depending on housing type, location variation, and changes over time.